Analisis Strategi Pemasaran dan Pengalaman Pelanggan pada UMKM Aneka Keripik Muzzaki - Mulyani Mulyani; Siti Titta Partini; Destiyanti Destiyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the marketing strategies implemented and customer perception of MSMEs of Various Muzzaki Chips in Subang Regency. This study uses a qualitative descriptive approach with a case study method. Data is collected through interviews with MSME owners, employees, and customers, which are then analyzed to identify the effectiveness of marketing strategies and customer perception of the products and services provided. The focus of the research includes the implementation of marketing strategies based on the concept of Segmenting, Targeting, and Positioning (STP), as well as the 4P (Product, Price, Place, Promotion) marketing mix. In addition, the evaluation of customer perception is carried out based on five dimensions of service quality, namely Tangibility, Empathy, Responsibility, Responsiveness, and Assurance. The results of the study show that MSMEs Aneka Keripik Muzzaki have implemented the STP strategy on target, namely targeting consumers aged 15-45 years, including students, employees, and housewives. The marketing mix strategy used is quite effective, starting from the development of innovative and quality products, affordable pricing, distribution through direct and online channels, and promotion through social media such as WhatsApp and Instagram. Customer perception of MSMEs tends to be positive, as can be seen from their satisfaction with the taste, packaging, price, and service provided. These results reflect the success of the marketing strategy implemented in building customer loyalty and increasing business competitiveness. It is recommended that MSMEs continue to improve the quality of products and services and expand their marketing reach through digital platforms to achieve sustainable growth.